2021
DOI: 10.3389/fgene.2021.775369
|View full text |Cite
|
Sign up to set email alerts
|

Somatic piRNAs and Transposons are Differentially Expressed Coincident with Skeletal Muscle Atrophy and Programmed Cell Death

Abstract: PIWI-interacting RNAs (piRNAs) are small single-stranded RNAs that can repress transposon expression via epigenetic silencing and transcript degradation. They have been identified predominantly in the ovary and testis, where they serve essential roles in transposon silencing in order to protect the integrity of the genome in the germline. The potential expression of piRNAs in somatic cells has been controversial. In the present study we demonstrate the expression of piRNAs derived from both genic and transposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…In recent years, however, the transcription of retrotransposons in somatic cells has shown to be tightly connected to cancer progression, neuronal defects, and brain development (Loreto & Pereira, 2017;Evans & Erwin, 2021). Studies in ageing suggest that loss of posttranslational histone marks in elder individuals results in increased transposon activity and susceptibility to cancer and neuronal degradation (Loreto & Pereira, 2017;Tsuji et al, 2021). Traditionally, posttranslational histone modifications with known links to transcriptional repression (e.g., H3K9 methylation) have been studied with regards to repression of transposon activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, the transcription of retrotransposons in somatic cells has shown to be tightly connected to cancer progression, neuronal defects, and brain development (Loreto & Pereira, 2017;Evans & Erwin, 2021). Studies in ageing suggest that loss of posttranslational histone marks in elder individuals results in increased transposon activity and susceptibility to cancer and neuronal degradation (Loreto & Pereira, 2017;Tsuji et al, 2021). Traditionally, posttranslational histone modifications with known links to transcriptional repression (e.g., H3K9 methylation) have been studied with regards to repression of transposon activity.…”
Section: Discussionmentioning
confidence: 99%
“…The processes leading to transposon activity have traditionally been studied in the germline because only these cells can pass their modified genomes to the offspring. However, a series of recent studies put the spotlight on transposon activity in somatic cells by linking it to disease, cellular ageing, cancer, and developmental processes, for example, brain development (Faulkner & Garcia-Perez, 2017;Loreto & Pereira, 2017;Evans & Erwin, 2021;Tsuji et al, 2021). To repress transcription of transposable elements, organisms have evolved adaptive surveillance and interference systems consisting of short noncoding PIWI-interacting RNA (piRNA)-binding Argonaut class proteins to cleave transposable element transcripts in a sequence-specific manner (Czech & Hannon, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relevance of piRNAs to the homeostasis of fully differentiated tissues, in particular skeletal muscle, is almost completely unknown. A recent study reported that piRNA expression was lost during the programmed degeneration of intersegmental muscles of Manduca sexta , suggesting that piRNAs might play a role in the regulation of muscle mass 18 . Given their direct contribution to genome stabilization during germ cell generation, it is assumed that piRNAs contribute to genomic stability also in adult stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence is positioning piRNAs as relevant epigenetic regulators, and studies have demonstrated their relevance to the progression of some diseases 17 . Some recent pieces of evidence indicate that piRNAs might be important during muscle atrophy 18 . Yet, to our knowledge, no characterization of sncRNA signatures in the skeletal muscle exists in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation